Effect of F-Actin Organization in Lamellipodium on Viscoelasticity and Migration of Huh-7 Cells Under pH Microenvironments Using AM-FM Atomic Force Microscopy - Chen, Miao; Zhu, Wenpeng; Liang, Zhihua; Yao, Songyou; Zhang, Xiaoyue; Zheng, Yue (Frontiers in Physics, 2021)
Cytoskeleton is responsible for fundamental cellular processes and functions. The filamentous actin (F-actin) is a key constituent of the cytoskeleton system which is intrinsically viscoelastic and greatly determines the mechanical properties of cells. The organization and polymerization of F-actin are relevant to the viscoelasticity distribution and the migration of living cells responding to pH microenvironments. Recently, progression in various diseases such as cancers have been found that cellular migration is related to the alterations in the viscoelasticity of lamellipodium. However, the correlation among F-actin organization, viscoelastic properties and cellular migration of living cancer cells under different pH microenvironments are still poorly understood. Conventional experimental methods of optical microscopy and atomic force microscopy (AFM) can neither break the trade-off between resolution and rate in cytoskeleton imaging, nor achieve the structural characterization and the mechanical measurement simultaneously. Although multifrequency AFM with amplitude modulation-frequency modulation (AM–FM) enables us to probe both the surface topography and the viscoelasticity distribution of cells, it is difficult to image the cytoskeletal filaments with the diameter down to the scale of tens of nanometers. Here, we have improved the AM-FM AFM by employing the high damping of cell culture medium to increase the signal-to-noise ratio and achieve a stable imaging of F-actin with the resolution down to 50 nm under in situ microenvironment. The approach that can successfully visualize the structures of cytoskeletal filaments and measure the distribution of mechanical properties simultaneously enable us to understand the relationship between the organization of F-actin and the viscoelasticity of living Huh-7 cancer cells under different pH values. Our experimental results have demonstrated that, unlike the randomly distributed F-actin and the homogeneous viscoelasticity at the normal pH level of 7.4, the living Huh-7 cancer cells with the reduced pH level of 6.5 show highly oriented and organized F-actin along the lamellipodium direction associated with the significant gradient increase both in elasticity and viscosity, which are confirmed by immunofluorescence confocal microscopy. The F-actin organization and the gradient viscoelasticity of lamellipodium provide structural and mechanical understanding on the adhesion and migration of living cancer cells that undergo metastasis and malignant transformation.